Obregón y Villa en el espejo autobiográfico - Viveros Anaya, Luz América (El Colegio de México, 2021)
This paper aims to compare the discursive and publishing strategies of two works pertaining to the “autobiographical sphere”: Álvaro Obregón’s Ocho mil kilómetros en campaña (1917) and Regino Hernández Llergo’s interview with Pancho Villa in 1922, which appeared in El Universal. The factual “veritative” reading of both texts has undoubtedly had consequences in Mexican history. Obregon’s piece, based on war reports, letters, telegrams, first-hand accounts and so on, was used throughout decades to validate one side of the story. Likewise, the interview with Villa has come to be seen as the cause of his assassination.